The Cause-Forming Analysis of Shangping Tungsten Deposit - Zhengru Gan (Global Journal of Earth Science and Engineering, 2017)
The forming of each deposit has its objective and natural conditions. Different deposits have different types because their conditions and environments are different. This paper analyzed and discussed the cause of Shangping tungsten deposit. Firstly, it is the district background. Secondly, it is the geological characteristics and the age of the deposit. We think that the deposit is the zoning deposit of intermittently reverse precipitation from the pegmatite petrography to the hydrothermal solution stage gradually from the whole developing process. And this is a more complicated high temperature hydrothermal solution deposit of (FeMn) WO4 and quartz with thin-vein type from the characteristics of the deposit. The cause classification from different was is new and original in the paper. Its aim is to finding out the distribution regulation of the tungsten deposit and to serve for directing mine production and prospecting bitterly.